Predicting stock price movements from past returns: the role of consistency and tax-loss selling - Grinblatt, Mark; Moskowitz, Tobias J. (Journal of Financial Economics, 2004)
The consistency of positive past returns and tax-loss selling significantly affects the relation between past returns and the cross-section of expected returns. Analysis of these additional effects across stock characteristics, seasons, and tax regimes provides clues about the sources of temporal relations in stock returns, pointing to potential explanations for this relation. A parsimonious trading rule generates surprisingly large economic returns despite controls for confounding sources of return premia, microstructure effects, and data snooping biases.